The person of Jesus Christ - Mackintosh,H.R. (Hugh Ross),1870-1936; Torrance, T.F. (Edinburgh : T & T Clark, 2000)
The person of Jesus Christ first published in 1912 by the Student Christian Movement.
Keywords: Jesus Christ -- Person and offices